Prehabilitation for Patients Undergoing Orthopedic Surgery - Niken, Niken; Yudith, Yudith (The Indonesian Journal of General Medicine, 2024)
Background: The literature surrounding prehabilitation for patients undergoing orthopedic surgery has evolved significantly over recent years, highlighting its potential to enhance surgical outcomes through a multifaceted approach. Literature Review: Following this, (L. Waterland et al., 2021) conducted a systematic review and meta-analysis that highlighted the immediate postoperative benefits of prehabilitation, specifically regarding functional exercise capacity and hospital length of stay. The article by (H. Koh et al., 2021) further contributes to this discourse by focusing on the benefits of prehabilitation in mitigating sarcopenia among elderly patients. (H Koh et al., 2021) show that a structured presurgery prehabilitation program can improve surgical outcomes and reduce costs for aged patients. The integration of nutritional and psychosocial components into prehabilitation programs is advocated by (Paladini et al., 2023). Finally, (Ma et al., 2024) provide a bibliometric analysis that charts the evolution of prehabilitation research from 2005 to 2023. This review identifies emerging trends in the literature, particularly concerning malnutrition and frailty among older patients. Conclusion: In conclusion, the reviewed literature collectively underscores the growing recognition of prehabilitation as a vital component of surgical care, particularly for at-risk populations. It advocates for personalized, multimodal approaches that integrate physical, nutritional, and psychological interventions to enhance patient outcomes and optimize recovery processes in the context of orthopedic surgery.